(3GdCehGds - (3CHh LYaQ CMeO Hf fUQ GdOGhOj GdeGdcj, GdOGhOj,J (B307 (3g` s ((3eMeO Hf eMeO Hf YHO GdQMef GdebHdi s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ , GdYRjR GdZaGQ , Gdedc GdLHGQ f NGdb Gddjd hGdfgGQ PcQ eG jLQi Ydi CjOi GdCeQGA ef GdCehGd s
(3BNQgG (B:s
(3hGdMeO ddg Ydi eG ef Hg YdjfG ef cJGHg GdPi dG jCJjg GdHGWd ef Hjf jOjg hdG ef Ndag hef SfI QShd Gddg hUdi Gddg Ydi eMeO fHjg Ydjg GdSdGe ced GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B264s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdeGdcjs